ACCIDENT RISK CONTROL IN CHEMICAL LABORATORY THROUGH THE INTRODUCTION OF MSDS AND HS FOR CHEMISTRY TEACHERS IN EAST ACEH - Jofrishal Jofrishal; Rahmatul Fajri (Global Science Society, 2022)
This training program aims to introduce Material Safety Data Sheet (MSDS) and Hazardous Sign (HS) of chemical and regulations of them to chemistry teachers in the East Aceh district. The method of carrying out the activities begins with the literature study, building communication with the chemistry teacher discussion group (MGMP) of chemistry, training activities, monitoring program achievements and evaluating the benefits of the program in supporting practical activities in schools. Based on the results of the activity, it was found that the teacher's understanding of the MSDS and HS after attending the training activities was very good, this was seen from the enthusiasm of the teacher in participating in their activities and active involvement in discussions. Based on the results of monitoring and evaluation, it was found that the teacher in conducting the practicum had been more careful and studied the MSDS of the materials used first, so that the benefits of the training activities could be felt by students and other laboratory users. East Aceh chemistry teachers have committed to applying the results of training activities in practical activities in schools sustainably and consistent, then we hope the number of laboratory accidents can be reduced.